Salt Resistance Characteristics of Winter Wheat Varieties in Soil and Climatic Conditions of Bukhara Region - Rahim qizi, Teshayeva Dilfuza (European Journal of Life Safety and Stability (2660-9630), 2021)
The task of providing the population of our country with food and grain products is a very important one. The decrees and instructions of the President of the Republic of Uzbekistan on the development of agriculture during the years of independence have played an important role in solving this problem. In particular, the Decree of March 24, 2003 "On the most important directions of deepening reforms in agriculture." The decree stipulates the establishment of a special council to address the issue of "grain development" as one of the most important sectors of agriculture. Wheat is one of the most valuable and productive food crops. Its grain is rich in gluten proteins and is not inferior in quality to water wheat. B.P. According to Pleshkov, the protein content of wheat grain is 9 to 26%, nitrogen-free extracts 49 to 73%, fats 1.5 to 3%, klechatka 2.5%, ash 1.3 to 2.8 % varies relative to grain weight. Vitamins in wheat contain thiamine (B1) - 5.5 mg / kg, ciacin (PP) - 63.6 mg / kg, riboflavin - 1.3 mg / kg, pantothenic acid - 13.6 mg / kg. Its flour is used to make fresh, nutritious, fragrant, nutritious dark and white breads.